Accurate axillary staging by superparamagnetic iron oxide-enhanced MRI at 1.5 T with fat-suppression sequence as an alternative to sentinel node biopsy in breast cancer. Issue 11 (24th August 2021) - Motomura, K; Tabuchi, Y; Enomoto, Y; Nishida, T; Nakaoka, T; Mori, D; Kouda, M
Abstract : Superparamagnetic iron oxide (SPIO)-enhanced MRI at 1.5 T with fat-suppression sequence is useful for the detection of metastases in sentinel nodes localized by CT lymphography in patients with breast cancer. SPIO-enhanced MRI may offer an alternative to sentinel node biopsy and avoid axillary surgery itself for patients with breast cancer who have negative sentinel nodes on SPIO-enhanced MRI.